Importance of potentially inappropriate medications, number of chronic conditions and medications for the risk of hospitalisation in elderly in Sweden: a case–control study. Issue 9 (27th September 2019) - Thorell, Kristine; Midlöv, Patrik; Fastbom, Johan; Halling, Anders
Abstract : Objectives: This study aimed to investigate the importance of potentially inappropriate medications, number of medications and chronic conditions for the risk of hospitalisation among an elderly population. Design: This is a case–control study. Setting: Population-based study in 2013 of all individuals aged 75 years and older (17 203) in the county of Blekinge in the southeast of Sweden. Participants: A total of 2941 individuals were included who had at least one hospitalisation to a medical, geriatric and palliative, or orthopaedic ward during 2013. From this total, 81 were excluded because of incomplete data or absence of controls. In total, 5720 patients were included and formed 2860 risk sets matched on age and gender. Primary and secondary outcome measures: Conditional logistic regression was used to analyse the odds for hospitalisation according to use of potentially inappropriate medication (PIM), number of chronic conditions and medicines using univariate and multivariate models. PIM was defined as long-acting benzodiazepines, tramadol, propiomazine and medicines with anticholinergic effect. Results: The univariate analysis for use of PIM showed a significant association with hospitalisation (OR 1.54, 95% CI 1.30 to 1.83). For the number of chronic conditions, the OR was increased and was significant from two or more chronic conditions, and for the number of medicines from the use of five or more medicines, in the univariate analysis. Use of PIM has no association with hospitalisation in the full model. The number of chronic conditions and medicines in the full models continued to have strong associations for hospitalisation, from five to seven chronic conditions (OR 1.86, 95% CI 1.49 to 2.33) and use of five to nine medicines (OR 1.46, 95% CI 1.21 to 1.77) at the same time. Conclusion: The number of chronic conditions and medications are important for the odds of hospitalisation, while the use of PIM, according to the definition used in this study, was no significant in the full model.